MODEL PEMBIMBINGAN AKADEMIK ONLINE BAGI MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS TERBUKA - Muhammad Husni Arifin; Yulia Budiwati; Daryono Daryono (LPPM Universitas Terbuka, 2009)
Academic counseling in Higher Distance Education is one of the necessary instructional media between the faculty and the students as well as an important device for assisting students to cope and solve their problems. Up until now academic counseling has not been extensively used by lectures and students at the Universitas Terbuka because of a number of constraints such as unavailability of time, the disperse of student domicile and technological barriers. This study attempts to explore and examine the role of on-line academic counseling at Universitas Terbuka in particular at the Faculty of Social and Political Sciences (FISIP-UT). The finding shows that most students consider academic counseling as highly important to support student achievement. Accordingly online academic counseling needs to be more flexible and covers broader area. Online academic counseling needs a separate on-line forum aside the exciting forums such as online learning forum, smart teachers online, digital libraries, online bookstores, e-humanities, and learning object repositories. However, it is expected to be regularly scheduled and prompt response is imperative.